Cancer in Cumbria and in the vicinity of the Sellafield nuclear installation, 1963-90. Issue 6870 (9th January 1993) - Draper, G J; Stiller, C A; Cartwright, R A; Craft, A W; Vincent, T J
Abstract : OBJECTIVE–To reappraise the epidemiological findings reported by the Black Advisory Group concerning a possible excess of malignant disease, particularly of childhood acute lymphoid leukaemia and non-Hodgkin lymphomas, in the vicinity of the Sellafield nuclear installation, and to determine whether any excess of malignant disease had occurred among people aged 0-24 years in the area in the years after the Black report–that is, from 1984 to 1990. DESIGN–Calculation of incidence of cancer using data from population based cancer registries and special surveys. SETTING–England and Wales; county of Cumbria; county districts Allerdale and Copeland within Cumbria; Seascale ward within Copeland. SUBJECTS–All residents under the age of 75 years in the above areas, but with particular reference to those aged 0-24 years. MAIN OUTCOME MEASURES–Numbers of cases and incidence particularly of lymphoid leukaemia and non-Hodgkin lymphomas in those aged 0-24 years, but including other cancers and age groups. RESULTS–Previous reports of an increased incidence of cancer, especially of leukaemia, among those aged 0-24 years in Seascale during the period up to and including 1983 are confirmed. During 1984-90 there was an excess of total cancer among those aged 0-24 years. This was based on four cases including two cases of non-Hodgkin lymphoma but none of leukaemia. There was an increased, but nonsignificant, incidence of other cancers, based on two cases (one pinealoma and one Hodgkin's disease) occurring among those aged 15-24 years during 1984-90. This was not observed in the younger age group or in previous years. For the immediately surrounding area–that is, the county districts of Allerdale and Copeland excluding Seascale and in the remainder of Cumbria–there was no evidence of an increased incidence of cancer among those aged 0-24 years in either period. CONCLUSIONS–During 1963-83 and 1984-90 the incidence of malignant disease, particularly lymphoid leukaemia and non-Hodgkin lymphomas, in young people aged 0-24 in Seascale was higher than would be expected on the basis of either national rates or those for the surrounding areas. Although this increased risk is unlikely to be due to chance, the reasons for it are still unknown.